Cardiac rehabilitation and 5-year mortality after acute coronary syndromes: The 2005 French FAST-MI study - Pouche, Marion; Ruidavets, Jean-Bernard; Ferrières, Jean; Iliou, Marie-Christine; Douard, Hervé; Lorgis, Luc; Carrié, Didier; Brunel, Philippe; Simon, Tabassome; Bataille, Vincent; Danchin, Nicolas (Archives of cardiovascular diseases, 2016)
Clinical studies have shown a beneficial effect of cardiac rehabilitation (CR) on mortality. To study the effect of CR prescription at discharge on 5-year mortality in patients with acute myocardial infarction (AMI). Participants, from the 2005 French FAST-MI hospital registry, were 2894 survivors at discharge, divided according to AMI type: ST-segment elevation myocardial infarction (STEMI; n=1523) and non-STEMI (NSTEMI; n=1371). The effect of CR prescription on mortality was analysed using a Cox proportional hazards model. At discharge, 22.1% of patients had a CR prescription. Patients referred to CR were younger (62.4 vs. 67.5years), were more frequently men and more had presented with STEMI (67.8% vs. 48.3%) than non-referred patients. Ninety-four (14.7%) deaths occurred among patients referred to CR and 585 (25.9%) among non-referred patients (P<0.001). After multivariable adjustment, the association between CR and mortality remained significant (hazard ratio [HR] 0.76, 95% confidence interval [CI] 0.60–0.96). Analyses stratified by sex, age (<60 vs.≥60years) and AMI type showed that the inverse association was stronger in men (HR 0.64, 95% CI 0.48–0.87) than in women (HR 0.95, 95% CI 0.64–1.39), in younger (HR 0.34, 95% CI 0.15–0.77) than in older patients (HR 0.84, 95% CI 0.65–1.07) and in NSTEMI (HR 0.63, 95% CI 0.46–0.88) than in STEMI (HR 0.99, 95% CI 0.69–1.40). After hospitalization for AMI, referral to CR remains a significant predictor of improved patient survival; some subgroups seem to gain greater benefit. Différents travaux ont montré un effet bénéfique de la réadaptation cardiaque (RC) sur la mortalité. Nous avons étudié l’impact sur la mortalité à 5ans de la prescription de RC chez des patients admis pour infarctus du myocarde aigu (IM). Les participants du registre hospitalier FAST-MI conduit en 2005, étaient les 2894 survivants après hospitalisation dont 1523 IM avec sus-décalage du segment ST et 1371 sans sus-décalage. L’impact de la prescription de RC sur la mortalité a été analysé en utilisant le modèle de Cox. À la sortie de l’hôpital, 22,1 % des patients avaient une prescription de RC. Les patients adressés en RC étaient plus jeunes (62,4 vs 67,5ans), plus fréquemment des hommes et ont présenté plus d’IM avec sus-décalage (67,8 % vs 48,3 %) que les non-adressés. Il y a eu 94 décès (14,7 %) parmi les patients adressés en RC et 585 (25,9 %) chez les non-adressés (p<0,001). Après ajustement multivarié, l’association entre la RC et la mortalité reste significative (0,76 [0,60–0,96]). L’analyse stratifiée sur le genre, l’âge (<60 vs≥60ans) et le type d’infarctus a montré que l’association était plus forte chez les hommes (0,64 [0,48–0,87]) que chez les femmes (0,95 [0,64–1,39]), chez les plus jeunes (0,34 [0,15–0,77]) que chez les plus âgés (0,84 [0,65–1,07]) et pour les IM avec sus-décalage (0,63 [0,46–0,88]) que sans sus-décalage (0,99 [0,69–1,40]). Après hospitalisation pour IM aigu, la RC améliore significativement la survie des patients à moyen terme et quelques sous-groupes de patients semblent avoir un meilleur bénéfice.